MEDB-03. Medulloblastoma cerebrospinal fluid reveals hypoxic indicators (metabolites and lipids) and cancer-specific RNAs. (3rd June 2022) - Lee, Bongyong; Mohamad, Iqbal; Pokhrel, Rudramani; Murad, Rabi; Yuan, Menglang; Stapleton, Stacie; Bettegowda, Chetan; Jallo, George; Eberhart, Charles G; Garrett, Timothy; Perera, Ranjan J
Abstract: Medulloblastoma (MB) is the most common malignant brain tumor in children. There remains an unmet need for diagnostics to sensitively detect the disease, particularly recurrences. Cerebrospinal fluid (CSF) provides a window into the central nervous system, and liquid biopsy of CSF could provide a relatively non-invasive means for disease diagnosis. There has yet to be an integrated analysis of the transcriptomic, metabolomic, and lipidomic changes occurring in the CSF of children with MB. CSF samples from patients with (n=40) or without (n=11; no cancer) MB were subjected to RNA-sequencing and high-resolution mass spectrometry to identify RNA, metabolite, and lipid profiles. Differentially expressed transcripts, metabolites, and lipids were identified and their biological significance assessed by pathway analysis. Multivariate analysis method DIABLO (R package mixOmics) was used to integrate the molecular changes characterizing the CSF of MB patients. Differentially expressed transcripts, metabolites, and lipids in CSF were discriminatory for the presence of MB but not the exact molecular subtype. One hundred ten genes and ten circular RNAs were differentially expressed in MB CSF compared to normal representing TGF-β signaling, TNF-a signaling via NF-kB, and adipogenesis pathways. Tricarboxylic acid cycle and other metabolites (malate, fumarate, succinate, α-ketoglutarate, hydroxypyruvate, N-acetyl-aspartate) and total triacylglycerols were significantly upregulated in MB CSF compared to normal CSF. Although the transcriptomic, metabolomic, and lipid signatures in CSF to differentiate MB subgroup separation was challenging, we were able to identify a group of omics signatures that could separate cancer from normal CSF. Metabolic and lipidomic profiles both contained indicators of tumor hypoxia. Our approach provides several candidate signatures that deserve further validation, including the novel circular RNA circ_463, and insights into the impact of MB on the CSF microenvironment.